Reduced tubuloglomerular feedback activity and absence of its synchronization in a connexin40 knockout rat - More, Heather L.; Braam, Branko; Cupples, William A. (Frontiers in Network Physiology, 2023)
Tubuloglomerular feedback (TGF) is the negative feedback component of renal blood flow (RBF) autoregulation. Neighbouring nephrons often exhibit spontaneous TGF oscillation and synchronization mediated by endothelial communication, largely via connexin40 (Cx40). To investigate this, we had a knockout (KO) rat made that lacks Cx40. One base pair was altered to create a stop codon in exon 1 of Gja5, the gene that encodes Cx40 (the strain is WKY-Gja5 5em1Mcwi ).Breeding from heterozygotes, the distribution of wild type (WT), heterozygote, and KO pups at weaning approximated the Mendelian ratio of 1:2:1; growth did not differ among the three strains. The KO rats were hypertensive. Blood pressure (BP)-RBF transfer functions probed RBF dynamics and indicated low gain of the myogenic mechanism and a smaller TGF resonance peak in KO than in WT rats. Laser speckle imaging interrogated the dynamics of efferent arterioles that reach the surface (star vessels). The myogenic mechanism had higher frequency in KO than in WT rats, but similar maximum spectral power. In contrast, the frequency of TGF was similar while peak power of its oscillation was much smaller in KO than in WT rats. In WT rats, plots of instantaneous TGF phase revealed BP-independent TGF synchronization among star vessels. The synchronization could be both prolonged and widespread. In KO rats TGF synchronization was not seen, although BP transients could elicit short-lived TGF entrainment. Despite the reduced TGF spectral power in KO rats, there was sufficient TGF gain to induce oscillations and therefore enough gain to be effective locally. We conclude that failure to synchronize is dependent, at least in part, on impaired conducted vasomotor responses.